2010
DOI: 10.28945/1133
|View full text |Cite
|
Sign up to set email alerts
|

Clickers in the Laboratory: Student Thoughts and Views

Abstract: Many methods are used to enhance student engagement in instructional nursing education courses, and systems are introduced as new technologies become available. The aim of this research was to evaluate student's experiences of the use of an Audience Response System (ARS) -aka Clickers -in the laboratory setting and determine if it improved student knowledge retention and contributed to the body of research in this area. Students used handheld RF devices to respond to PowerPoint questions in relation to wound c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…"Once they know their ranking they can see that people have a higher ranking than themselves or better skills and some students will be attracted to that.If that's not presented nobody knows their position in the class and they might think they are the best student, and they're not.They might think they're the worst student, and they're not as well" (Interview 17). This finding fits with the literature which argues that audience response systems (aka clickers) help motivate and engage students while simultaneously providing feedback on students' understanding of material [39].…”
Section: F Principle 6: Communicates High Expectationssupporting
confidence: 75%
“…"Once they know their ranking they can see that people have a higher ranking than themselves or better skills and some students will be attracted to that.If that's not presented nobody knows their position in the class and they might think they are the best student, and they're not.They might think they're the worst student, and they're not as well" (Interview 17). This finding fits with the literature which argues that audience response systems (aka clickers) help motivate and engage students while simultaneously providing feedback on students' understanding of material [39].…”
Section: F Principle 6: Communicates High Expectationssupporting
confidence: 75%
“…Research indicates that student motivation to learn increases when partaking in learning and when immediate feedback is provided because students are able to be certain of their understanding about the content discussed in class (Johnson & Lillis, 2010). According to the teacher's observation journal, students in the trial group were able to make more connections to their prior knowledge.…”
Section: Finding #2 Student Participation and Motivationmentioning
confidence: 99%
“…2,35 Additionally, LAP improves participation, motivation and understanding, 21,36,37 and lecture topics that are discussed using interactive devices result in students being more engaged, focused and interested. 9,[38][39][40][41] It has been reported that the discussion sparked by LAP is one of its most important benefits, as students prefer to respond individually prior to open group discussion of answers.…”
Section: Discussionmentioning
confidence: 99%